Inclusive Instructional Practices: Course Design, Implementation, and Discourse - Salehi, Shima; Ballen, Cissy J.; Trujillo, Gloriana; Wieman, Carl (Frontiers in Education, 2021)
As national efforts strive to make STEM more inclusive, it is important to identify instructional practices that maximize effective learning for all and provide students from different demographic and educational backgrounds equal opportunities to excel. Here, we present a guideline for inclusive instructional practices based on findings from 1) cognitive psychology about learning and memory, 2) social psychology about creating inclusive discourse, and 3) discipline-based education research (DBER) about effective learning practices in STEM higher education. Our aim is to promote equity across STEM education by providing researchers and instructors across different STEM fields with concrete suggestions for implementing inclusive instructional practices in their courses.